Which medical disciplines diagnose and treat melanoma in Europe in 2019? A survey of experts from melanoma centres in 27 European countries. (10th February 2021) - Kandolf‐Sekulovic, L.; Peris, K.; Stratigos, A.; Hauschild, A.; Forsea, A.‐M.; Lebbe, C.; Lallas, A.; Grob, J.‐J.; Harwood, C.; Gogas, H.; Rutkowski, P.; Olah, J.; et al.
Abstract: Background and objectives: The incidence of melanoma is increasing. This places significant burden on societies to provide efficient cancer care. The European Cancer Organisation recently published the essential requirements for quality melanoma care. The present study is aimed for the first time to roughly estimate the extent to which these requirements have been met in Europe. Materials and methods: A web‐based survey of experts from melanoma centres in 27 European countries was conducted from 1 February to 1 August 2019. Data on diagnostic techniques, surgical and medical treatment, organization of cancer care and education were collected and correlated with national health and economic indicators and mortality‐to‐incidence ratio (MIR) as a surrogate for survival. Univariate linear regression analysis was performed to evaluate the correlations. SPSS software was used. Statistical significance was set at P  < 0.05. Results: The MIR was lower in countries with a high health expenditure per capita and with a higher numbers of general practitioners (GPs) and surgeons (SURG) per million inhabitants. In these countries, GPs and dermatologists (DER) were involved in melanoma detection; high percentage of DER used dermatoscopy and were involved in the follow‐up of all melanoma stages; both medical oncologists (ONC) and dermato‐oncologists administered systemic treatments; and patients had better access to sentinel lymph node biopsy and were treated within multidisciplinary tumour boards. Conclusion: Based on these first estimates, the greater involvement of GPs in melanoma detection; the greater involvement of highly trained DER in dermatoscopy, dermatosurgery, follow‐up and the systemic treatment of melanoma; and the provision of ongoing dermato‐oncology training for pathologists, SURG, DER and ONC are necessary to provide an optimal melanoma care pathway. A comprehensive analysis of the melanoma care pathway based on clinical melanoma registries will be needed to more accurately evaluate these first insights.